Achieving long-lived room-temperature phosphorescence via charge transfer technology and dopant-matrix design strategy. (February 2023) - Ding, Shuhui; Xu, Yaxian; Li, Junbo; Wang, Xuepu; Wang, Guangming; Li, Haodong; Ren, Shixue; Zhang, Kaka
Abstract: Unlike heavy atom effect and n-π* transition that would increase both k ISC and k P, here we report that charge transfer technology and dipole effect can significantly enhance k ISC and simultaneously allow long-lived room-temperature phosphorescence ( τ P, 1.2 s) in dopant-matrix systems. The luminescent difluoroboron β-diketonate (BF2 bdk) dopants show intramolecular charge transfer characters in S1 state and possess multiple phenyl groups to enrich their excited state natures. Some Tn states mediate the intersystem crossing of BF2 bdk dopants to give T1 state with significant portion of localized excitation characters. The crystalline matrices selected are found to suppress nonradiative decay and oxygen quenching of the T1 state, leading to long-lived and bright room-temperature phosphorescence materials. This strategy based on charge transfer technology and dopant-matrix design would pave the way for constructing high-performance afterglow materials. Highlights: Bright afterglow materials were obtained via charge transfer technology and dopant-matrix strategy. The design strategy avoids the use of heavy atom effect and n-π* transition. The difluoroboron β-diketonate dopants exhibit 1.2 s phosphorescence lifetimes in phenyl benzoate matrices.